The influence of Service Quality, Promotion, and Brand Image on Decision Making of Gojek Service Users to Students in Tembalang - Dandi David Nababan; Makmun - Riyanto; Paniya - Paniya (Politeknik Negeri Semarang, 2020)
This study aims to determine the effect of Service Quality, Promotion, and Brand Image on Decision Making of Gojek Service Users (A Case Study of Students Using Gojek Services in Tembalang Semarang). The data collection method is done by literature review and using a questionnaire. The questionnaire used is the Agree-Disagree Scale with a scale of 10. The sampling method using a purposive sampling method of 150 samples. Data processing is conducted using SPSS 24. Based on the calculations that have been done, the results of the t test show that each variable accepts Ha1, Ha2, dan Ha3, so that the variables of Service Quality (X1), Promotion (X2), and Brand Image (X3) have a significant effect on the use decision variable (Y). The F test shows that Ho4 is rejected and Ha4 is accepted, which means that the variables of Service Quality (X1), Promotion (X2), and Brand Image (X3) simultaneously influence the Use Decision variable (Y). Then the results of the determination coefficient test show a value of 0.605, which means that 60.5% of the Use Decision variable (Y) can be explained by the variables of Service Quality (X1), Promotion (X2), and Brand Image (X3) and the remaining 39.5% is influenced by factors others who were not included in this study